Does Strict Adherence to the Ponseti Method Improve Isolated Clubfoot Treatment Outcomes? A Two-institution Review - Miller, Nancy H. (Clin Orthop Relat Res, 2015)
BACKGROUND: Despite being recognized as the gold standard in isolated clubfoot treatment, the Ponseti casting method has yielded variable results. Few studies have directly compared common predictors of treatment failure between institutions with high versus low failure rates. QUESTIONS/PURPOSES: We asked: (1) is the provider’s rigid adherence to the Ponseti method associated with a lower likelihood of unplanned clubfoot surgery, and (2) at the institution that did not adhere rigidly to Ponseti’s principles, are any demographic or treatment-related factors associated with increased likelihood of unplanned clubfoot surgery? METHODS: After institutional review board approval, a consecutive series of patients with a diagnosis of isolated clubfoot who underwent treatment between January 2003 and December 2007 were identified. At Institution 1, 91 of 133 patients met the eligibility criteria and were followed for a minimum of 2 years compared with 58 of 58 patients at Institution 2. At Institution 1, 16 providers managed care using a conservative casting approach based on the Ponseti method. However, treatment was adapted by the provider(s). At Institution 2, one orthopaedic surgeon managed care with strict adherence to the Ponseti method. Surgical indications at both institutions included the presence of a persistent equinovarus foot position while standing. A chart review was used to collect data related to proportion of patients undergoing unplanned additional treatment for deformity recurrences after Ponseti casting, demographics, and treatment patterns. RESULTS: The proportion of subjects who underwent unplanned major surgical intervention was greater (odds ratio [OR], 51.1; 95% CI, 6.8–384.0; p < 0.001) at Institution 1 (60 of 131, 47%) compared with Institution 2 (two of 91, 2%). There was no difference (p = 0.200) in the proportion of patients who underwent additional casting, repeat tendo Achilles lengthening, and/or anterior tibialis tendon transfer only (minor recurrence) at Institution 1 (nine of 131, 7%) compared with Institution 2 (11 of 91, 13%). At Institution 1, an increase in the number of revision casts (multiple vs no casts, hazard ratio [HR] = 3.9; 95% CI, 2.0–7.6; p < 0.001) and an increase in the number of cast-related complications (multiple vs no complications, HR = 2.8; 95% CI, 1.2–6.7; p = 0.019) were associated with increased risk of major surgery in the multivariate analysis. CONCLUSIONS: Rigid commitment to the Ponseti method in the conservative treatment of patients with isolated clubfoot was associated with a lower risk of subsequent unplanned surgical intervention. In addition, clubfoot treatment programs that use a care model that prioritizes continuity in care and dedication to the Ponseti method may decrease the proportion of patients who undergo unplanned surgical intervention. LEVEL OF EVIDENCE: Level III, therapeutic study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-015-4559-4) contains supplementary material, which is available to authorized users.